Production of biofunctionalized MoS2 flakes with rationally modified lysozyme: a biocompatible 2D hybrid material. (6th July 2017) - Siepi, Marialuisa; Morales-Narváez, Eden; Domingo, Neus; Monti, Daria Maria; Notomista, Eugenio; Merkoçi, Arben
Abstract: Bioapplications of 2D materials embrace demanding features in terms of environmental impact, toxicity and biocompatibility. Here we report on the use of a rationally modified lysozyme to assist the exfoliation of MoS2 bulk crystals suspended in water through ultrasonic exfoliation. The design of the proposed lysozyme derivative provides this exfoliated 2D-materail with both, hydrophobic groups that interact with the surface of MoS2 and hydrophilic groups exposed to the aqueous medium, which hinders its re-aggregation. This approach, clarified also by molecular docking studies, leads to a stable material ( ζ -potential, 27 ± 1 mV) with a yield of up to 430 µ g ml −1 . The bio-hybrid material was characterized in terms of number of layers and optical properties according to different slots separated by diverse centrifugal forces. Furthermore the obtained material was proved to be biocompatible using human normal keratinocytes and human cancer epithelial cells, whereas the method was demonstrated to be applicable to produce other 2D materials such as graphene. This approach is appealing for the advantageous production of high quality MoS2 flakes and their application in biomedicine and biosensing. Moreover, this method can be applied to different starting materials, making the denatured lysozyme a promising bio-tool for surface functionalization of 2D materials.